Effect of ivermectin concentration on internal parasite control and the productive performance of bovine (Veterinary Science, 2017)
The aim of this study was to evaluate the efficacy of treatment with increasing doses of ivermectin on the parasite load, expressed as the number of eggs in faeces and the effect on heifers weight gain in a cattle ranch in San Pedro Department, Paraguay. They were selected out of 200 heifers hybridized (Bos taurus * Bos indicus) from randomly divided over year in the order of entry into four lots with 50 animals each, which were identified and weighed individually. Control Treatment: 1% ivermectin antiparasitic, Group A: treated with ivermectin at a concentration of 3.15% (Laboratory A); Group B: treated with ivermectin at a concentration of 3.15% (Laboratory B); Lot C: treated with ivermectin at a concentration of 4% was taken from each group a random subsample of 10 animals each and were extracted faeces samples being coincident with the first product application and then every 30 days we proceeded to take faeces samples of the animals so as to obtain the evolution of the number of eggs response. Were evaluated simultaneously live weights of the animals in each period. There were no statistical differences for weight gain (Wg) per period or the entire test. No statistical differences were observed for parasite control variable (Pc) corresponding to the total number of eggs per gram of collected faeces
Keywords: Avermectins; antiparasitic; dose; deworming